STATUS KUALITAS HIDUP MANTAN PENGGUNA NAPZA DAN BUKAN MANTAN PENGGUNA NAPZA DI PUSAT REHABILITASI NURUL HAROMAIN, YAYASAN AL ISLAMI, TETIRAH DZIKIR DAN RUMAH SAKIT GRHASIA MENGGUNAKAN SF-36 - , DAVID DWI PUTERA, Dra. Suhartini, Apt, S.U ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Backgrounds: The numbers of drug abusers in Indonesia are increasing. Rehabilitation is one of many ways to restore the physical and mental function due to the drug abuse. Measuring the quality of life of patients who are under the rehabilitation program is needed to know the outcome of the therapy. The numbers of researches about quality of life (QoL) and drug abuse are still low. Objectives: This research were conducted to assess the QoL of the patients in Nurul Haromain Rehabilitation Center, Yayasan Al Islami, Tetirah Dzikir and Grhasia Hospital